Un encuentro entre río y metro : un baile hecho danza (2017)
The Document of Process and Synthesis (DPS), is delivered as a memory of the architectural degree project, in the Advanced Unit of the University of Andes. On the front page is the title of the project, "Un Encuentro entre Río y Metro: Un Baile hecho Danza", words that let your imagination move and glimpse from faraway, before they make any sense. As you will see, the project will appear in the last pages, because my intention is to reveal it slowly, to relate in some way how I reach it. The following pages seeks to exalt the value of the road, the journey that is undertaken in an architectural project. Where there's space for particular processes, that get feed with events, with the interpretation of the subject, with the voices of those who accompany him. A process that dilutes the limits of architecture to return to it with more emotion, with an intention, that stays in each stroke.--Tomado del Formato de Documento de Grado.